(untitled) (Research, Society and Development, 2022)
In the last decades, an increasing number of individuals considered obese has been observed, thus becoming a public health problem. Among the various types of treatments found to solve this problem, the drug sibutramine is found in the field of medicines. Research has shown different effects to this drug, especially cardiovascular ones. Therefore, the present study aimed to describe the therapeutic efficacy of sibutramine and present the advantages and risks of this drug to obese individuals. The study is based on a literature review, which was based on scientific works already published between the years 2017 to 2021 in Portuguese and English and that specifically deal with the proposed theme. Data collection took place in a database, such as the Virtual Health Library (VHL), Lilacs, Scielo, PubMed, and Google Scholar. Initially, it obtained 87 previously selected articles, the search resulted in 70 articles after using the inclusion and exclusion criteria; 20 articles remained for analysis, interpretation and discussion. In the results, it was evident that, from the studies found, sibutramine proved to be effective for the treatment of obesity, in the face of good medical and pharmaceutical follow-up, as well as good adherence by patients, associating the use of medication with healthy habits. and physical activity.